Pernikahan Lintas Agama Muslim dengan Non Muslim Perspektif Hukum Islam - Herdiansyah Herdiansyah; Novyar Satriawan Fikri; Syariffuddin Syariffuddin (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
AbstractMarriage is a means of social and divine interaction. Islam strongly recommends that marriage relations must be accompanied by an element of equivalence or harmony. One of the elements of equivalence or harmony is in terms of religious beliefs. This research was conducted with the aim of knowing (1) how is the view of Islamic law in addressing interfaith marriages between Muslims and non-Muslims; (2) what are the social impacts of interfaith marriages between Muslims and non-Muslims. This research is a type of library research, by examining and reviewing sources from books and literature related to the issues discussed, or other supporting sources. The final conclusion of this study: First, interfaith marriages between Muslims and non-Muslims when viewed from the perspective of Islamic law can be divided into four categories, along with their respective laws. Second: regarding what is meant by Ahlul Kitab women who are allowed to marry Muslim men, there are many differences of opinion among scholars, there are some who forbid it on the grounds that Ahlul Kitab are also polytheists, but the majority of scholars still allow it, some allow it with conditions and there are also allowed it unconditionally. Third: it is permissible for a Muslim man to marry a Biblical woman with the intention that he is able to influence his wife and children to embrace Islam, because he tends to have power. Fourth: If viewed from a benefit perspective, the marriage of a Muslim man to a Muslim woman who is muhshanah at the moment is Indonesian scholars, especially through the fatwa of the Indonesian Ulema Council (MUI) forbidding this marriage. The social impact of interfaith marriages between Muslims and non-Muslims will harm the values of Islamic religious teachings, and will greatly affect the domestic life between husband and wife as well as the process of education and upbringing of their offspring.